UNVEILING CONSUMER BEHAVIOR: THE INFLUENCE OF PRICE, VALUE, AND APPEARANCE ON REPURCHASE INTENTIONS WITH A HALAL PERSPECTIVE - Vidyaningrum Dwisetya Vardani; Rahardja, Conny Tjandra (LPPM STIE YKPN Yogyakarta, 2024)
This study aims to analyze the influence of Price Perception, Perceived Value, and Appearance Perception on Repurchase Intention, with Halal Perception as a moderating variable among consumers of Mixue Ice Cream & Tea in the Special Region of Yogyakarta. The sample consists of consumers who have purchased Mixue Ice Cream & Tea more than four times, are Muslim, and reside in the Special Region of Yogyakarta. Data collection was conducted using Google Forms to distribute the questionnaires. Data processing and hypothesis testing were performed using SmartPLS 4 software. The hypothesis test results indicate that Price Perception, Perceived Value, and Appearance Perception have a positive and significant effect on Repurchase Intention. The moderation test results show that Halal Perception does not moderate the effect of Price Perception on Repurchase Intention, nor does it moderate the effect of Perceived Value on Repurchase Intention. However, Halal Perception does moderate the effect of Appearance Perception on Repurchase Intention.